2020
DOI: 10.1590/1980-0037.2020v22e67000
|View full text |Cite
|
Sign up to set email alerts
|

Influence of overweight on functional capacity of physically active older women

Abstract: Aging comprises a dynamic and progressive process, characterized by physiological and functional changes. Among these changes, increase in body fat is considered relevant, since it can leads to impaired physical fitness and augmented cardiometabolic risks. Considering this, the objective of this study was to evaluate the influence of overweight on functional capacity of physically active older women. A field survey was performed with 24 older women who practiced physical exercise. Participants were submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Studies have veri ed that aging decreases the exibility [19]. In particular, the BMI and exibility in female older adults exhibit a signi cant negative correlation, which indicates that overweight and obesity reduce the exibility [20][21][22]. This study used interference factors to adjust and compute odds ratios; the ndings revealed that the lower exibility scores are associated with higher overweight or obese risks.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Studies have veri ed that aging decreases the exibility [19]. In particular, the BMI and exibility in female older adults exhibit a signi cant negative correlation, which indicates that overweight and obesity reduce the exibility [20][21][22]. This study used interference factors to adjust and compute odds ratios; the ndings revealed that the lower exibility scores are associated with higher overweight or obese risks.…”
Section: Discussionmentioning
confidence: 83%
“…Results 21,630 participants aged 65 to 96 years with complete data were included from Taiwan's National Physical Fitness Examination Survey Databases (35.38 % of men). Demographic characteristics and anthropometric variables are presented in Table 1.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Studies have veri ed that aging decreases the exibility [17]. In particular, the BMI and exibility in female older adults exhibit a signi cant negative correlation, which indicates that OW and obesity reduce the exibility [18][19][20]. This study used interference factors to adjust and compute odds ratios; the ndings revealed that in OW and OB older adults in Taiwan, different obesity levels signi cantly in uenced their chair sit-and-reach and back scratch test scores.…”
Section: Discussionmentioning
confidence: 94%